PELATIHAN BAHASA INGGRIS BAGI PEMANDU WISATA DI DESA PELANGAS KECAMATAN SIMPANG TERITIP KABUPATEN BANGKA BARAT - Risdandi, Bayu; Ramadhani, Herni; Majah, Ibnu; Iman Aulia, Lailatul; Ananda, Mellisa; Yolanda, Nova; Ramadhan, Sahrul; Afza Nabilla, Sheilla; Khofifah Lestari, Siti; Yusmita, Yusmita; Rachma Kurniasi, Eka (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Increasing the interest in tourist villages by both local and foreign tourists with the increase in human resources in the field of communication, especially communicating in English as the language most widely used as a liaison when communicating with foreign travelers. The members of the Pelangas Village Pokdarwis are hosts for visitors to the Sabong hill tour who must master the ability to speak good English. The purpose of this KKN activity is to organize training to help Pokdarwis members improve their English skills. Based on the results of observations and interviews conducted before the program started, Pokdarwis members still do not have good skills in communicating using English for the benefit of travelers. In solving these problems, one good solution is through training methods or courses using English, namely by practicing/practicing directly using English in interacting with foreign travelers, outlining the potential for natural tourism, accommodation and equipment facilities for travelers. Based on the results of the field questionnaires given to the training participants, there were no obstacles or difficulties encountered in participating in this training. Pokdarwis and the Village Head felt very helpful with the English language training for tour guides, most of the participants could understand well all the material provided. The participants also realized the importance of deepening their English language skills, especially communication skills